Consumer Protection Against Side Effects of Beauty Clinic Services Without Specialist Doctors Based On Law Number 8 Of 1999 Concerning Consumer Protection - Armansyah, Roy; Satino, Satino (Journal of Law, Politic and Humanities, 2024)
As technological advancements in the health sector have led to increased demand for beauty clinic services, many beauty clinics are now offering their services without the involvement of specialized doctors. This practice poses significant health risks to consumers, especially regarding possible illegal actions. Based on Law No. 8/1999 on Consumer Protection, this research investigates the legal protection of consumers in relation to beauty clinic services that do not use specialist doctors. By using a normative juridical method with a statutory approach, and reviewing regulations related to consumer health and safety, including Law No. 17 of 2023 on health. The results of this study show that beauty clinics that do not involve specialist doctors in their services often violate applicable legal standards, especially in terms of the obligation to provide services that are safe and according to medical standards. Consumers who suffer losses due to these services have the right to file a lawsuit, in accordance with the provisions listed in Article 19 and Article 45 of the Consumer Protection Law. This research confirms the need for regulations governing beauty clinics, especially regarding the certification and competence of medical personnel who provide services to ensure the fulfillment of consumer rights to security and safety in using beauty services.